The association between post-lunch napping duration and social participation among the Chinese older adults: a cross-sectional study - Xiaozhen Fu; Rong Lin; Yuanjiao Yan; Chenshan Huang; Bingjie Wei; Hong Li (BMC Geriatrics)
Abstract Background Social participation (SP) affects the physical and mental health of older adults. Post-lunch napping is a prevalent lifestyle practice observed among older adults, and it may have an impact on their SP. However, research that explores the association between these factors is limited, and we thus aimed to examine this association. Methods We conducted a cross-sectional study using data from the China Health and Retirement Longitudinal Study (CHARLS), focusing on participants aged 60 and older. SP was measured by both the number and frequency of activities based on participant self-reports. The duration of post-lunch napping was also self-reported. We explored the association between post-lunch napping duration and SP using logistic regression, subgroup analysis, and Restrictive Cubic Spline (RCS) analysis. Results We included 4259 participants in the study. Post-lunch napping demonstrated a significant association with decreased odds ratio of poor SP in fully adjusted logistic regression models (odds ratio = 0.77, 95% CI: 0.66 ~ 0.90, p = 0.011). Subgroup analysis indicated consistent proportional effects across all subgroups (p > 0.05). RCS analysis revealed a non-linear "J"-shaped relationship between post-lunch napping duration and SP, with the lowest odds ratio corresponding to a duration of 34.37 min. Conclusion Our study suggests that a moderate duration of post-lunch napping, ideally around 34 min, might have the potential to enhance SP, whereas exceeding this duration could could potentially have a limiting effect. This observation implies that incorporating moderate post-lunch napping into health management strategies for older adults might offer some advantages.